calculati
( √3 - √12 )² - ( √7 + √11 ) ( √11 - √7)
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
(√3 -√12)² - (√7 +√11) (√11 -√7)=
= (√3-2√3)² -(√11 +√7) (√11 -√7)=
=(-√3)²- (√11²-√7²)=
=3- (11-7)=
=3-4=
=-1
Răspuns de
7
Răspuns:
Explicație pas cu pas:
( √3 - √12 )² - ( √7 + √11 ) ( √11 - √7) =
(√3 )² - 2·√3·√12 + (√12)² - (√11 + √7 ) · (√11 - √7) =
3 - 2·√36 + 12 - (√11 + √7 ) · (√11 - √7) =
3 - 2·√(6²) + 12 - [(√11)² - (√7)²] =
3 - 2·6 + 12 - (11 - 7) =
3 - 12 + 12 - 4 =
3 - 4 = -1
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă